Hadith Interpretation of Law and Justice and Its Implementation as an Alternative Solution Rule of Law Enforcement In Indonesian - Rahman, Rahman; Sugianto, Efendi; Wasalmi, Wasalmi; Asriady, Muhammad; Fauzi, Ahmad (IAIN Ponorogo, 2023)
AbstractThis article wants to explain the interpretation of hadith on law and justice and its implementation as an alternative solution to upholding the supremacy of law in Indonesia. This aims to address the social gap in law enforcement in Indonesia which is characterized by the increasing number of law violations due to a lack of firmness in law enforcement itself. This research is library research, namely library research, because all primary data is written data, especially those related to the Prophet's hadith about law and justice and their interpretation in the context of upholding the supremacy of law in Indonesia. The main sources are hadith books which are also featured in other cases relevant to the research. The results of this research indicate that the Prophet's hadith regarding law and justice can be implemented in the context of law enforcement in Indonesia because law enforcement during the time of the Prophet as described in the Prophet's hadith contained the principles of justice in society. When a crime is committed by a lawbreaker, the law can treat it as fairly as possible. AbstrakArtikel ini ingin menjelaskan tafsir hadis hukum dan keadilan serta implementasinya sebagai alternatif solusi tegaknya supremasi hukum di Indonesia. Hal ini bertujuan untuk menjawab kesenjangan sosial dalam penegakan hukum di Indonesia yang ditandai dengan semakin banyaknya pelanggaran hukum akibat kurangnya ketegasan dalam penegakan hukum itu sendiri. Penelitian ini merupakan penelitian kepustakaan yaitu penelitian kepustakaan, karena seluruh data primernya merupakan data tertulis, khususnya yang berkaitan dengan hadis Nabi tentang hukum dan keadilan serta penafsirannya dalam rangka penegakan supremasi hukum di Indonesia. Sumber utamanya adalah kitab-kitab hadis yang juga ditampilkan dalam kasus-kasus lain yang relevan dengan penelitian. Hasil penelitian ini menunjukkan bahwa hadis Nabi tentang hukum dan keadilan dapat diimplementasikan dalam konteks penegakan hukum di Indonesia karena penegakan hukum pada masa Nabi yang telah dijelaskan dalam hadis Nabi mengandung prinsip-prinsip keadilan di tengah-tengah masyarakat. ketika suatu kejahatan terjadi dilakukan oleh pelanggar hukum, maka hukum itu dapat memperlakukan dengan seadil-adilnya